PERBANDINGAN EFISIENSI BAK PROSES DUA SEL DAN TIGA SEL DALAM MENURUNKAN KANDUNGAN BESI (Fe) DALAM AIR LIMBAH SECARA ELEKTROKOAGULASI DENGAN KATODA DARI KARBON BEKAS BATERAI - Sutanto Sutanto (Politeknik Negeri Jakarta, 2011)
The content pollutants of iron (Fe) in waste water that uncontrolled can cause environmental pollution. Iron content in the waste water that exceeds 1 mg / L is not safe for the environment. Because the regulation of the Minister of Environment No.Kep-03/MENKLH/II/1991 explained that the maximum content of iron in the waste water is 1 mg / L If the iron content in the waste water exceeds that of such provision, the waste water must be treated until comply with the regulations of the Ministry of Environment. One of the processing carried out in this research is to apply the electrocoagulation process with aluminum as anode and waste carbon baterry as cathode. The research is conducted by flowing water of 7 liters of industrial waste water into the bath electrocoagulation process. The process is runing in the two and three cell of tank with an power electric 12 V and intervals of 2 minutes for observation iron content in waste water. The iron content in waste water is analyzed by Atomic Absorption Spectrophotometer (AAS). The results of process until 28 minutes showed that the iron content is reduced from 4.23 mg/L to 0.91 mg/L or equivalent with 78.49 % for process in two cells and from 4.23 mg/L to 0.33 mg/L or equivalent with 92.20 % for process in three cells. Conclusion, the efficiency of the three cells is the best than two cells to reduced iron content in the waste water. Keywords:Waste water, Pollutant of Copper,Electrocoagulation,Reduction of Pollutant